THE INFLUENCE OF PRODUCT QUALITY AND PROMOTION ON PURCHASE DECISIONS IN THE TIKTOK SHOP ON THE TIKTOK APPLICATION IN THE PGRI MAHADEWA INDONESIA UNIVERSITY ENVIRONMENT - Ayu, Lusia Ayu Anggraini; Ni Luh Putu Yesy Anggreni; I Ketut Sudana (Arthaniti Studies, 2024)
This research aims to determine the influence of product quality and promotions on purchasing decisions at the TikTok shop on the TikTok shop application within the PGRI Mahadewa University, Indonesia. This research uses a quantitative approach through a questionnaire method that took 93 respondents. The results of this research show that (1) There is a partially significant influence between product quality variables on purchasing decisions as seen from the t-test of 14.955 > ttable 1.98 with a significance value of (0.000 < 0.05); (2) There is a partial significant influence between promotional variables on purchasing decisions as seen from the t-test results of 12.254 > ttable 1.98 with a significance value of (0.000 < 0.05); (3) There is a significant simultaneous influence between product quality and promotion variables on purchasing decisions as seen from the Fcount test results of 127.915 < Ftable 3.10 with a significance value of (0.000 < 0.05). The results of the coefficient of determination show that the R Square is 0.740, which means that 74.0% of purchasing decision variables are influenced by product quality and promotion while the remaining 26.0% are influenced by various factors outside the research model.